AN EVOLUTION OF PROPERTY RIGHT REGIME OF CORAL REEF MANAGEMENT: FROM AN OPEN ACCESS, TO STATE PROPERTY REGIME AND SUSTAINABLE LOCAL GOVERNANCE - A LESSON FROM GILI INDAH VILLAGE, WEST LOMBOK, INDONESIA - Aceng Hidayat (JOURNAL OF COASTAL DEVELOPMENT, 2005)
This paper is to explain a case of evolution of property right regime of coral reef management: from an open access to state property and then to local governance, a case study of Gili Indah West Lombok, Indonesia. It demonstrates the reasons of change, the ineffectiveness of state property regime, and the emergence of local governance where conflicts are assumed as the triggering factors. The study found out that conflict of interest between two main stakeholders: tourism business operators (TBOs) and fishermen drove the change process. The conflicts initialLv emerged after Balai Konservasi Sumberdaya Alam (BKSDA) as the executor of the state property regimes was unable to protect the coral reef ecosystems from destructive fishing practice. It has also failed in halting Muroami application that has triggered lasting conflicts between TBOs and fishermen. The failure of the state property regime has led TBOs to take over the protection tasks through constructing local governance. So far, the local governance has been successful in protecting the coral reef resources and forced the users to use the coral reek in a sustainable manner. However, it still shows a number of weaknesses in dealing with new challenges such as the non-involvement of several stakeholders in making social agreements and the unequal distribution of authority and responsibility among the actors and stakeholders. Therefore, attempts to find an alternative regime that could address the new challenges ofthe reef management are still required